2019
DOI: 10.1038/s41598-019-42116-x
|View full text |Cite
|
Sign up to set email alerts
|

Periocular skin warming elevates the distal skin temperature without affecting the proximal or core body temperature

Abstract: Periocular skin warming reportedly improves the objective and subjective sleep quality in adults with mild difficulty in falling asleep. To clarify the effects of periocular warming, we examined the distal skin temperatures (hands and feet), proximal skin temperature (infraclavicular region) and core body temperature as well as the distal-proximal skin temperature gradient (DPG). Nineteen healthy males underwent two experimental sessions, wherein they used a warming or sham eye mask under a semi-constant routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The removal of the heat source may have prevented further decreases in the pulse rate. The effects of the three interventions on the pulse rate were similar to the effect of the warming EM observed in a previous study [7], with no appreciable differences among the three groups.…”
Section: Physiological Indicatorssupporting
confidence: 83%
See 2 more Smart Citations
“…The removal of the heat source may have prevented further decreases in the pulse rate. The effects of the three interventions on the pulse rate were similar to the effect of the warming EM observed in a previous study [7], with no appreciable differences among the three groups.…”
Section: Physiological Indicatorssupporting
confidence: 83%
“…This explains the observed elevation of axillary temperature at the end of and 10 min after the intervention compared with that before the intervention in all three groups. Previous studies using the warming EM have reported that the warming EM signi cantly increased the distal skin temperatures (hands and feet) without affecting the proximal skin temperature (infraclavicular region) or core body temperatures and provoked physiological heat loss [6,7]. The elevation of axillary temperature in the present study may not be attributable to the heat stimuli only and is consistent with a previous study showing that neither the truncal skin temperature nor the core body temperature was in uenced by the periocular warming [6].…”
Section: Physiological Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a preliminary study, we demonstrated that periocular skin warming improves subjective sleep initiation in healthy individuals with mild difficulty falling asleep ( 15 ). In addition, periocular skin warming during the daytime in healthy men has been demonstrated to increase the distal skin (hands and foot) temperature and DPG, resulting in the promotion of sleep onset in a laboratory environment ( 16 , 17 ). Considering that periocular skin warming has similar thermoregulatory effects on sleep as distal skin warming, periocular skin warming might be safely and easily employed at home as a treatment option for insomnia disorder.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that periocular skin warming induced psychological and physiological relaxation [11] and improved the subjective and objective quality of sleep [12, 13]. Possibly, warm steam inhalation may have similar beneficial effects on sleep quality through psychological relaxation.…”
Section: Introductionmentioning
confidence: 99%